Chronology of the LAGs formation and body growth in argenteohyla siemersi from northeastern Argentina - Piñeiro, Jose Miguel (2018)
We studied the chronology of LAG formation and validated the method for estimate age in Argenteohyla siemersi inhabiting the humid Chaco of Argentina. In addition, we determined whether well-expressed growth marks are formed in A. siemersi when raised during one year in laboratory, to determine whether formation is genetically or environmentally based. Individuals increased 84.51% in BM and 52.47% in SVL after one year of growth in the laboratory. Two out of eight individuals that survived at the end of the experiment showed well-expressed growth marks. Overall, we confirm the reliability of the skeletochronology in estimating age of this specie and reinforce the hypothesis that, the LAG formation is ultimately caused by a general intrinsic (genetic) control.